2011
DOI: 10.1002/ange.201104357
|View full text |Cite
|
Sign up to set email alerts
|

Anion‐Assisted Supramolecular Polymerization: From Achiral AB‐Type Monomers to Chiral Assemblies

Abstract: Control over the self-assembly process of monomeric species by functional group modulation is highly desirable in the context of supramolecular polymer design. These materials, unlike covalently linked polymers, consist of monomeric arrays held together by reversible and highly directional noncovalent bonds. [1] Owing to the dynamic and reversible nature of noncovalent interactions, supramolecular polymers display unique topologies and unconventional properties (such as stimuli responsiveness [2] and self-hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 90 publications
0
5
0
Order By: Relevance
“…The looser the ion-pairing interactions, the higher the DP. Furthermore, Gattuso et al demonstrated an elegant strategy to significantly enhance the DP by synthesizing a heteroditopic monomer, 40 , a calix[5]­aren derivative with an ancillary anion-binding site on the upper rim (Figure b) …”
Section: Driving Forces For Supramolecular Polymersmentioning
confidence: 99%
See 1 more Smart Citation
“…The looser the ion-pairing interactions, the higher the DP. Furthermore, Gattuso et al demonstrated an elegant strategy to significantly enhance the DP by synthesizing a heteroditopic monomer, 40 , a calix[5]­aren derivative with an ancillary anion-binding site on the upper rim (Figure b) …”
Section: Driving Forces For Supramolecular Polymersmentioning
confidence: 99%
“…DOSY is becoming a popular method for characterization of supramolecular polymers. ,, The diffusion coefficient is inversely proportional to the size of supramolecular polymers. Furthermore, the size of supramolecular polymers can be qualitatively estimated according to the Stokes–Einstein equation.…”
Section: Characterization Of Supramolecular Polymersmentioning
confidence: 99%
“…For the synthesis of the title compound, see: Stewart et al (1995). For calix [5]arene molecules derived from the title compound, see: Garozzo et al (2005); Capici et al (2011); Pappalardo et al (2012). For the structures of calix [5]arene/ alkylammonium complexes, see: Gattuso et al (2012).…”
Section: Related Literaturementioning
confidence: 99%
“…19 Our work conrmed the crucial role played by the encapsulation of potassium ion within the cryptand-like binding site of this calix [4]tube derivative in the noncovalent synthesis of discrete porphyrin-calixarene nanostructures. 19 Inspired by the self-assembly motif 3,20-24 of tetraurea-calix [4] arenes, and in alignment with our focus on designing linear supramolecular polymers, [25][26][27][28][29][30][31] we decided to shi our attention towards investigating the supramolecular properties of ureacontaining calix [4]tubes.…”
Section: Introductionmentioning
confidence: 99%